Extraction of Algae Oil from Nannocloropsis sp.: A study of Soxhlet and Ultrasonic-Assisted Extractions - Wiyarno, Budi; Mohd Yunus, Rosli; Mel, Maizirwan (Asian Network for Scientific Information, 2011)
This study aims at describing the characteristics of the microalgae oil extraction from N annochloropsis sp. using soxhlet and ultrasonic. There were two extraction processes that were investigated,Soxhlet-assisted Extraction (SE) and Ultrasonic-assisted Extraction CUE) and both used ethanol solvent. A combination of several criteria was selected to find the characteristics of each extraction. In the SE, a variety of ethanol concentration and time were used; whereas in the UE, a variety of ethanol volwne, time and temperature were applied. The given frequency for all DE treatments was 40 kHz. The quality of algae oil proceeded by SE was shown by the level ofFF A (Free Fatty Acid) and saponification number. In the SE study, the best combination was gained when the ethanol concentration was 70% and the given time was 200 min in which the FFA level was 9.4% and the saponification mnnber was 286.8. While in the DE study, 51.6 min, 98% of ethanol concentration and 69.62°C were the best circwnstance in which the quantity of the oil yield got its maximwn. In SE, the higher solvent concentration, the higher FF A level and saponification nwnber were gained. However, after reaching the peak at particular circwnstance, the saponification nwnber decreased gradually. Meanwhile, DE reduced the length of extraction time.